Podstawowe zmiany w prawie spółdzielczym w świetle projektowanej ustawy - Niedbała, Zdzisław (Wydział Prawa i Administracji UAM, 1994)
The paper focuses on the fundamental elements of a draft of a bill (Seym paper 158) which brings about modifications to the "Cooperative Law" of 1982, and subsequent modifications of the draft.
Fundamental Changes in the Cooperative Law in the light of the draft of new bill